Tantangan dan Peluang Pemerintah Daerah dalam Penanggulangan Kemiskinan - Muhammad, Fadel; ., Mahmudi (Unisia, 2010)
The problem of poverty and unemployment become tremendous challenge to be solved by local government in this autonomy and fiscal decentralization era. Through local autonomy and decentralization, there are obviously greater opportunities to localize the problem of poverty and to take action based on local condition and local contingency factors. Poverty alleviation program initiated by local government should be oriented to be more humanistic with dignity approach, that is taking people in poor as a subject to be enhanced and entrusted to be able to escape from their poverty problem. Through the concept of self-help community, the problem of poverty can be eradicated more effective. The big challenge faced by local government concerning to the poverty alleviation program is to develop strong political and economic democration in a local context. There are at least six pillars that need deep attention to be improved and enhanced, i.e. education, people income, health, regulation and law enforcement, public service infrastructure, and institutional building.